Common Teacher Mistakes in the Learning Outcome Evaluation Process: Implications for Evaluative Competency Development - Rindawan, Rindawan; Mujriah, Mujriah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to analyze and identify the types of evaluation errors commonly made by primary and secondary school teachers in Southwest Praya Sub-district and explore the impact of these errors on student motivation and development. The study also aimed to develop strategic recommendations for developing teachers' evaluative competencies. The main problems identified include difficulties in selecting appropriate evaluation techniques, mismatching questions with students' abilities, and teachers' low understanding in developing Higher-Order Thinking Skills (HOTS)-based questions. The study used a quantitative descriptive method with data collection through a questionnaire involving teachers as respondents. The results of the analysis showed that 75% of respondents experienced difficulties in choosing evaluation techniques, 80% considered the questions made were not in accordance with students' abilities, and 85% expressed a lack of understanding in developing HOTS-based questions. This finding confirms the need to increase teachers' capacity through structured training that focuses on preparing effective learning evaluations that meet students' needs. The contribution of this research is to provide practical recommendations for education policy makers to design more relevant professional development programs. The implications of the results of this study are expected to help improve the quality of learning evaluation at primary and secondary school levels, especially in the study area.